The effect of four-week high-intensity interval training on increasing physical fitness and specific speed in young Pencak Silat athletes - Subekti Nur; Mohammad Furqon Hidayatullah; Rony Syaifullah; Noor Alis Setiyadi; Anugrah Nur Warthadi (Sport TK)
This study aimed to determine the effect of high-intensity interval training (HIIT) on increasing aerobic performance and speed, specifically for Pencak Silat athletes. Thirteen student-level Pencak Silat athletes were selected using consecutive sampling methods and then divided into two groups: the experimental group (EG, n = 7) and the control group (CG, n = 6). The HIIT protocol on EG consists of 2 minutes x 3 sets, with a 1-minute rest interval between sets to adapt to the motion demands during the match. Yo-Yo Intermittent Recovery Test Level 1 (YYIR1) was used to measure aerobic performance capacity (VO2max) and FST to measure total kicks between pre- and post-HIIT. The results of the study showed that there was an increase in VO2max on EG (44.86±1.90 vs. 48.42±2.67 mL/kg/min; p=0.000) and CG (42.43±1.85 vs. 44.02±2.18 mL/kg/min; p=0.020). The mean delta in VO2max increased between the two groups, with a significant difference (p ≤ 0.05), and the EG produced a larger effect size compared to the CG. For total kicks, there was a substantial increase between pre-post on EG (105.72±7.89 vs. 112.57±8.91 n; p=0.001), while CG did not show any significant difference (p ≥ 0.05). These findings prove that the Pencak Silat-specific HIIT protocol can improve aerobic performance and speed specifically for Pencak Silat athletes.